A study on the layout design of the domestic portal site APPS - juLee, Hyun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Even just a few years ago, we took care of a lot of things through PC, from writing simple documents to checking our email and doing online shopping. But many of these tasks are now done on smart phones.Methods/Statistical analysis: It has become difficult to imagine a world without smart phones these days. This has led to all websites considering a smart phone environment when designing their sites. The layout which has the greatest range of change depending on the screen size is now an important element in design. As such, a comparative analysis was conducted on the layout design of the main screens of Naver and Daum, two of the leading portals in Korea.Findings: The layout of the mobile portal site by Naver and Daum had similar menus without a big difference. However, there was a slight difference to the menu laid out around the search window. First, Naver had the search window located immediately below the site name and the menu was laid out so that news could be viewed by category. The menu can be moved left and right to enter into the categories. Major articles are shown under the menu. Scrolling the entire window up and down allows you to move to a screen to see more information. Under major articles are photos considered hot topics under â€˜hot menu itemsâ€™. Below the photo is weather forecast in a large font size, which would be of interest to many users. Daum, too, has the search window under the main logo but unlike Naver, has the real-time search ranking under the search menu instead of the main menu. In addition, the main menu located under the real time search words draw attention with its head font and color of the logo. This can be moved left and right to expand the menu. The remaining structure is similar to that of Naver, consisting of major news, hot topic photos and weather forecasts.Improvements/Applications: There were almost no ornamental elements on the main page of Naver or Daum. There were only text and information, as well as related photos.Â Â